2005
DOI: 10.3141/1941-01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fuel Economy on Automobile Safety: A Reexamination

Abstract: Since 1975, the fuel economy of passenger cars and light trucks has been regulated by the corporate average fuel economy (CAFE) standards, established during the energy crises of the 1970s. Calls to increase fuel economy are usually met by a fierce debate on the effectiveness of the CAFE standards and their impact on highway safety. A seminal study of the link between CAFE and traffic fatalities was published by R. W. Crandall and J. D. Graham in 1989. They linked higher fuel economy levels to decreases in veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…There are widely differing estimates of oil use externalities (NRC, 2002;Lutter and Kravitz, 2003) and the safety impacts of reducing size and weight (Kahane, 2003;Van Auken and Zellner, 2003;Ross and Wenzel, 2002;Ahmad and Greene, 2005), so it is difficult to weigh these arguments. However, there is ample evidence that vehicle purchasers do not behave as ''rational consumers,'' at least in terms of how economists define such consumers.…”
Section: Rationale For Standardsmentioning
confidence: 98%
“…There are widely differing estimates of oil use externalities (NRC, 2002;Lutter and Kravitz, 2003) and the safety impacts of reducing size and weight (Kahane, 2003;Van Auken and Zellner, 2003;Ross and Wenzel, 2002;Ahmad and Greene, 2005), so it is difficult to weigh these arguments. However, there is ample evidence that vehicle purchasers do not behave as ''rational consumers,'' at least in terms of how economists define such consumers.…”
Section: Rationale For Standardsmentioning
confidence: 98%
“…Crandall and Grahams study from 1989 using aggregate data claim that the Corporate Average Fuel Economy (CAFE) program that requires a minimum fuel efficiency standard has led to lighter vehicles and thereby additional fatalities. Several studies have questioned Crandall and Grahams result (Ahmad and Greene, 2005) and especially emphasized that a replacement of cars by light trucks like SUVs has lead to more fatal accidents (White, 2004). Our model gives no support either to downsizing the vehicle fleet or upsizing it but suggests that it is the mass difference that should be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Kazzhoum (1994) critiqued Crandall and Graham and reran their analysis using data from 1985 to 1989, which generated the result that increased car weight caused the number of fatalities in single-car crashes to go up. Ahmad and Greene (2004) reexamined Crandall and Grahamʼs studies using data from 1966 to 2002, and found that the statistics could not support the assertion that increased fuel economy has led to a greater number of traffic fatalities.…”
Section: The Weight Confers Safety Argumentmentioning
confidence: 99%